Reinterpretasi Konsep Daulat dan Durhaka dalam Gurindam Dua Belas: Pergeseran Paradigma Kepemimpinan Melayu Klasik - Elmustian Elmustian; Hermandra Hermandra; Ika Apriyanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research deconstructs the concepts of daulat (sovereignty) and durhaka (treason) within the text of Gurindam Dua Belas by Raja Ali Haji, viewed through the lens of a paradigm shift in Classical Malay leadership. The central problem addressed is the tension between the traditional, sacred-supernatural conception of daulat and the Islamic ethical demands introduced by Raja Ali Haji. Utilizing a sociological hermeneutic method, this study focuses its analysis on the Fifth and Twelfth Articles to dissect the internal transformation of values. These specific articles are selected as they represent the core of leader-people relational ethics and individual moral responsibility. The findings reveal that in Raja Ali Haji’s thought, daulat underwent an Islamization process, evolving into a conditional